Advertising for Demand Creation for Voluntary Medical Male Circumcision. (15th August 2016) - Wilson, Nicholas; Frade, Sasha; Rech, Dino; Friedman, Willa
Abstract : Objective: To measure the effects of information, a challenge, and a conditional cash transfer on take-up of voluntary medical male circumcision (VMMC). Design: A randomized, controlled experiment with 4000 postcard recipients in Soweto (Johannesburg), South Africa. Methods: We examined differences in take-up of several decisions in the VMMC cascade between the control arm and each of several intervention arms using logistic regression. Results: Logistic regression analysis indicated that the group offered US $10 as compensation and the group challenged with "Are you tough enough?" had significantly higher take-up of the VMMC procedure than did the control group [odds ratios, respectively, 5.30 (CI: 2.20 to 12.76) and 2.70 (CI: 1.05 to 6.91)]. Similarly, the compensation group had significantly higher take-up of the VMMC counseling session than did the control group [odds ratio 3.76 (CI: 1.79 to 7.89)]. The analysis did not reveal significantly different take-up of either the VMMC counseling session or the procedure in the partner preference information group compared with the control group [odds ratios, respectively, 1.23 (CI: 0.51 to 2.97) and 1.67 (CI: 0.61 to 4.62)]. The analysis did not reveal significantly higher take-up of the VMMC nurse hotline in any intervention group compared with the control group [odds ratios for US $10, information, and challenge, respectively, 1.17 (CI: 0.67 to 2.07), 0.69 (CI: 0.36 to 1.32), and 0.60 (0.31 to 1.18)]. Conclusions: Among adult males in Soweto, South Africa, compensation of US $10 provided conditional on completing the VMMC counseling session compared with no compensation offer and a postcard with a challenge, "Are you tough enough?" compared with no challenge, resulted in moderate increases in take-up of circumcision.